Non-Dairy Fermented Beverages Produced with Functional Lactic Acid Bacteria - Medana Zamfir; Iulia-Roxana Angelescu; Catalina Voaides; Calina-Petruta Cornea; Oana Boiu-Sicuia; Silvia-Simona Grosu-Tudor (Microorganisms, 2022)
At present, there is an increasing interest in beverages of non-dairy origin, as alternatives to those based on milk, but having similar health-promoting properties. Fermentation with specific bacteria or consortia may enhance the functionality of these products. In our study, selected lactic acid bacteria, that have been previously shown to possess functional properties (antimicrobial activity, probiotic potential), were used for the fermentation of wheat bran combined with root vegetables. Strains were investigated for their safety, while the obtained beverages were characterized in terms of microbial content, physical, chemical, nutritional, and functional properties. None of the strains harbors virulence genes, but all of them possess genes for survival at low pH, starch metabolism, and vitamin biosynthesis. Three strains (Lactiplantibacillus plantarum BR9, L. plantarum P35, and Lactobacillus acidophilus IBB801) and two substrates (5% wheat bran with 10% red beetroot/carrots) were selected based on a preliminary assessment of the beverage’s sensory acceptability. These strains showed good growth and stability over time in the stored beverages. No enterobacteria were detected at the end of fermentations, while the final pH was, in most cases, below 3.5. Free phenolics, flavonoids, and DPPH scavenging effect increased during fermentation in all drinks, reaching 24h values that were much higher than in the unfermented substrates. Most of the obtained drinks were able to prevent the growth of certain pathogens, including Listeria monocytogenes ATCC 19111, Salmonella enterica ATCC 14028, Staphylococcus aureus ATCC 25923, and Escherichia coli ATCC 25922. The obtained beverages would combine the nutritiveness of the raw ingredients with the beneficial effect of fermentation (increasing shelf life, health-promoting effect, pleasant flavor, etc.). They would also fill a gap in the non-dairy probiotics sector, which is constantly increasing due to the increasing number of vegan people or people that cannot consume dairy products.